An Analysis of Profitability and Liquidity Position of Selected Auto Ancillaries Companies of India (with Special Reference to Tyres Manufacturing Companies) - Vyas Krishna (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2019)
The high development potential of the Auto Ancillary Industry of India makes it one of the sunrise industries in Indian market. That is the reason why researcher has chose to conduct research on this industry. In present research analysis on five auto ancillary companies manufacturing Tyre is carried out considering five years through ANOVA test and trend analysis using graph.